Encouraging Undergraduate Student Experiential Learning through a Community-Based Fall Risk Assessment and Prevention Clinic. (2nd January 2021) - Wood, Tyler A.; Richards, K. Andrew R.; Sosnoff, Jacob J.
ABSTRACT: Community engagement provides kinesiology undergraduate students with valuable experience and allows for personal and professional growth. Kinesiology students often seek out opportunities that pertain to their future career goals. As many of them aspire to allied health professions, working with special populations is of interest, including individuals with movement impairments. As a result of their knowledge of movement and physical activity, kinesiology students are uniquely qualified to quantify and prevent adverse events due to movement impairment, including falls. The purpose of this article is to overview undergraduate students' involvement in a community-based fall risk assessment and prevention clinic through the lens of experiential learning theory. Collectively, this type of program has the potential to enhance the undergraduates' educational experience and preparation for their future careers while also enriching the community with fall prevention resources.